Sustainable Development and Assessment of environmental impact - Pajtić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Sustainable development, determined by social, economic and environmental goals, comprises a balance of social, industrial and technological development on the one hand, and preserving and improving the environment on the other. In pursuing the principles of sustainable development a fundamental role of impact assessment and strategic environmental assessment. These are specifically prescribed procedure in accordance with generally accepted standard, with the participation of competent authorities and all interested persons with the same goal which is the preservation and improvement of the environment while achieving economic development. Estimates of the impact on the environment are mainly directed in part towards finding the optimal measures to prevent, mitigation or compensate damages. This work is dedicated to the positive legal regulations pertaining to this issue in our country, their compliance with relevant international regulations with special emphasis on the effect that they achieved, how to determine the necessary measures of prevention, mitigation and compensation of damages, their advantages and disadvantages.